HUBUNGAN PENGETAHUAN PRIMIGRAVIDA TENTANG HIPERTENSI KEHAMILAN DENGAN KEPATUHAN MELAKUKAN ANC DI BPS HJ. SITI FATIMAH, AMD.KEB KRIAN-SIDOARJO - Sari, Kurnia Indriyanti Purnama; Anggraeni, Widya (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2020)
ABSTRACT This reseach aimed to identify there is relation between knowledge of primigravida with compliance in doing ANC at BPS Hj. Siti Fatimah, Amd.Keb Krian Sidoarjo. Research design uses design cross sectional. Method sampling that used non probability sampling-concecutive sampling. Sample that taken as much as 28 respondents that is in mother primigravida that do pregnancy investigation at BPS Hj. Siti Fatimah, Amd.Keb At  Desa Terungkulon Kecamatan Krian Kabupaten Sidoarjo. This research data is taken by using kuesioner and observation sheet. After at existing data tabulation is analyzed by using test Spearman's Rho. Result of research show semi knowledge had by primigravida about pregnancy hypertension is at category less that is 14 responder (50%) and some of small have good knowledge that is 4 responder (14,29%). While compliance of primigravida in doing ANC most not regular that is 18 responder (64,29%) and almost regular half in doing ANC that is 10 responder (35,71%). From result of examination of statistic obtained by result of there is relation between knowledge of primigravida with compliance in doing ANC with correlation coefficient value equal to 0,548 with storey level of signification 0,003 ( < 0,05). Keyword: Knowledge Of Pregnancy Hypertension, compliance ANC.